Transient neonatal myasthenia gravis: a case report - Gentille Sánchez, Melissa (2025)
Transient neonatal myasthenia gravis (TNMG) is an acquired autoimmune disease that occurs in 10 to 20 % of newborns born to mothers with myasthenia gravis. Symptoms appear within the first 24-72 hours and disappear after weeks or months, with 90 % of patients achieving complete recovery by 2 months of age. The typical presentation begins with respiratory distress, generalized hypotonia, and feeding difficulties, requiring clinical surveillance from birth due to the possibility of early hospitalization. We present the case of a newborn, born to a mother with myasthenia gravis, who was admitted at 7 days of age to the Intermediate Care Unit of Hospital Nacional Arzobispo Loayza due to hypoactivity, poor sucking and hypotonia. Given the suspicion of TNMG due to the maternal history and the patient’s symptoms, a therapeutic anticholinesterase test was performed, showing immediate improvement in spontaneous activity and muscle tone, thereby confirming the diagnosis. The patient received treatment with subcutaneous neostigmine for 6 days, after which the regimen was changed to oral pyridostigmine to reduce the adverse effects caused by the previous drug. Finally, the patient was discharged at 26 days of age with favorable evolution and complete remission. TNMG is rare in newborns; the diagnosis is clinical, with the maternal history being of utmost importance. Likewise, it requires strict monitoring from birth to recognize signs and symptoms of the disease, enabling timely initiation of anticholinesterase treatment in moderate to severe cases, thus preventing long-term sequelae.